Lifetime reproductive effort is equal between the sexes in seed beetles (Callosobruchus maculatus): dispelling the myth of the cheap male. Issue 4 (4th July 2017) - Wagner, James D.; Bakare, Ajibola
Abstract : In the evolution of sexual reproduction, the development of asymmetrical gametes (anisogamy) often leads to the characterisation that males invest less in reproduction than females. This view is founded on the fact that male investment in individual gametes (sperm) and in gonadal tissue is often less than that of females. While it may be true that within a single mating interaction the relative reproductive investment by males and females differs, over their respective lifetimes an evolutionary view predicts that total lifetime reproductive investment should be the same for both sexes. We tested this prediction by measuring total reproductive investment in reproducing adult male and female seed beetles. Since seed beetle adults are facultatively aphagous, not needing to feed or drink as adults, we could track the daily loss of biomass in the reproducing adults as a proxy for total lifetime investment in maintenance and reproduction. By the end of their lifetime there was not a significant difference in total reproductive effort between males and females. Both sexes invested 70 ± 1% SE of their initial body mass in maintenance and reproduction. Altering sex ratios, creating male-biased or female-biased treatments, significantly influenced total investment between the sexes, but not in the manner predicted. Ours is one of the few studies that have measured total adult lifetime reproductive investment in an organism, and our results support the theoretical expectation of equal total reproductive investment between the sexes.